2020
DOI: 10.33314/jnhrc.v18i3.2499
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression among Patients with Thyroid Function Disorders

Abstract: Background: Psychiatric comorbidities are common in thyroid disorder patients and complicate patients’ life quality as well as disease management. We aimed to explore prevalence of anxiety and depression and identify associated characteristics among patients with thyroid function disorder. Methods: A descriptive, cross-sectional study was conducted on 129 thyroid disorder patients aged ?20 years. A semi-structured questionnaire, Beck Anxiety Inventory, and Beck Depression Inventory were used for sociodem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 0 publications
0
16
0
7
Order By: Relevance
“…Future studies addressing the long-term relationship between depression and cognition are still needed. Finally, many studies indicated that some neurological and endocrine conditions might affect the associations, for example, stroke (53,54) and hypothyroidism (55,56) might lead to both depression and cognitive impairment; however, such conditions were not considered in the present study. Additionally, some genetic factors were not included in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…Future studies addressing the long-term relationship between depression and cognition are still needed. Finally, many studies indicated that some neurological and endocrine conditions might affect the associations, for example, stroke (53,54) and hypothyroidism (55,56) might lead to both depression and cognitive impairment; however, such conditions were not considered in the present study. Additionally, some genetic factors were not included in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…Univariate analyses were conducted for all available sociodemographic and clinical variables. In order to select potentially meaningful organic conditions, we built a stepwise regression model predicting PHQ-9 total score, including all the pre-existing chronic medical conditions as possible predictors of depression (obesity, immunodepression, hypertension, dysthyroidism, cardiopathy, diabetes, cancer, inflammatory bowel diseases and vascular pathologies) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Obesity was considered as body mass index (BMI) > 30 (<18.5 underweight range, 18.5–24.9 healthy weight range, 25–29.9 overweight range, >30 obese range) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Os impactos da tireoidectomia vêm melhorando com os anos (3) , mas além dos aspectos funcionais pode haver impacto negativo na qualidade de vida em voz, com redução no pré operatório (2,6) , e alterações emocionais (3,(8)(9)(10) associadas ao diagnóstico dos nódulos tireoidianos.…”
Section: Introductionunclassified
“…Embora o papel da função tireoidiana nas alterações do humor seja pouco conhecido, existem evidências de que alterações tireoidianas levam a alterações emocionais (3,8) . Alguns estudos referem alta prevalência de ansiedade e depressão em pacientes com distúrbios da tireoide (8,9,11) , com o tempo de espera para realização da cirurgia e o peso do diagnóstico sendo determinantes na ansiedade/depressão do paciente (12) .…”
Section: Introductionunclassified